Bioaccumulation and histopathology of copper in Oreochromis mossambicus - Naigaga, Irene (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2003)
Cu is one of the most toxic elements that affect fish populations when the fish are exposed to concentrations exceeding their tolerance. To investigate the effects of elementary Cu on aspects of bioconcentration, histology and behaviour, O. mossambicus were exposed to 0 and 0.75 ± 0.20 mg/l of Cu for 96 hours (short-term study), and 0, 0.11 ± 0.02, 0.29 ± 0.02, and 0.47 ± 0.04 mg/l of Cu for 64 days (longterm study) under controlled conditions in the laboratory. For the long-term study fish were sampled for gills, liver, and kidney Cu accumulation analysis after 1, 32 and 64 days of exposure and after 1, 2, 4, 16, 32, and 64 days for gills, liver and spleen histology analysis. Cu accumulation was concentration-duration dependent with the highest accumulation capacity in the liver. A multifactor linear model was developed for the relationship between exposure dose, exposure duration and Cu accumulation in the organs with the liver model: Log L = 3.35 + 0.85W + 0.31T (r² = 0.892) giving a better fit than the gills: G = −35.09 + 10.58W + 17.58T (r² = 0.632). Where L = Cu accumulation values in the liver, G = Cu accumulation values in the gills (both in μg/g dry mass); W = exposure dose in water (mg/l); and T = exposure time (days). Using this model Cu accumulation in organs can be estimated when exposure concentration and duration is known. This model should be tested under different conditions to determine the potential of the model in monitoring Cu toxicity in the environment. Lesions were observed in the liver, gills and spleen in all Cu treatments at all exposure concentration and exposure durations. However, the incidence and the degree of alteration was related to the concentration of Cu and duration of exposure. The sequential appearance of lesions in the order of, hepatic vacuolar degeneration, fatty degeneration and necrosis indicated a gradual increase in liver damage with larger duration of exposure time and increasing Cu concentration. The initial lesions in the gills were manifested as hypertrophy and hyperplasia of the gill epithelium causing increase in the thickness of the secondary lamellae, mucous cell hypertrophy and proliferation, mucous hypersecretion, proliferation of eosinophilic granule cells and hyperplasia of interlamellar cells. With increase in exposure time, necrosis of the eosinophilic granule cells, lamellar oedema, epithelial desquamation and increase in severity of lamellar hyperplasia were observed. These lesions indicated an initial defence mechanism of the fish against Cu toxicity followed by advanced histological changes that were related to Cu concentration and duration of exposure. Changes in the spleen were haemosiderosis, increase in the white pulp and macrophage centres, reduction in the red pulp, and necrosis suggesting that fish exposed to environmentally relevant levels of Cu may be histopathologically altered leading to anaemia and immunosuppression. Regression analysis was used to quantify the relationship between the total activity of the fish, and duration of exposure. There was a gradual decline in fish activity related to Cu concentration and duration of exposure before introducing food into the tanks. There was a constant activity after introducing food in the tanks at the control and 0.11 ± 0.02 mg/l Cu exposure levels irrespective of exposure time. Analysis of covariance (ANCOVA) was used to test for the difference in slopes between treatments. There was no significant difference (p > 0.05) between slopes of the control and 0.11 ± 0.02 mg/l Cu, and between 0.29 ± 0.02 and 47 ± 0.04 mg/l Cu before and after introducing food in the tanks. The slopes of both the control and 0.11 ± 0.02 mg/l Cu were significantly different from those of 0.29 ± 0.02 and 0.47 ± 0.04 mg/l Cu (p < 0.05). There were significant differences in the mean opercular movements per minute between treatments (p < 0.05). There was hyperventilation at 0.11 ± 0.02 mg/l Cu i.e. 87 ± 18 opercular movements per minute (mean ± standard deviation) and hypoventilation at 0.29 ± 0.02 and 0.47 ± 0.04 mg/l Cu i.e. 37 ± 34 and 13 ± 6 opercular movements per minute compared to the control. Hypo- and hyperventilation were related to the lesser and greater gill damage, respectively. In conclusion Cu accumulation and effects on histology of the liver, gills and were related to the concentration of Cu in the water and duration of exposure showing a gradual increase in incidence and intensity with larger duration of exposure time and increasing Cu concentration. The fish were initially able to homeostatically regulate and detoxify Cu. However, as the exposure continued, the homeostatic mechanism appears to have failed to cope with the increasing metal burden causing advanced histological changes.
Keywords: Mozambique tilapia; Copper; Marine toxins; Fishes -- Effect of water pollution on; Water -- Pollution -- Environmental aspects